Search for Salmonella spp. in ostrich productive chain of Brazilian southeast region - de Freitas Neto, Oliveiro Caetano [UNESP]; Silva Lages, Sonia Luisa [UNESP]; Torres Carrasco, Adriano Oliveira; Berchieri Junior, Angelo [UNESP] (Springer, 2009)
We analyzed ostriches from an equipped farm located in the Brazilian southeast region for the presence of Salmonella spp. This bacterium was investigated in 80 samples of ostrich droppings, 90 eggs, 30 samples of feed and 30 samples of droppings from rodents. Additionally, at slaughter-house this bacterium was investigated in droppings, caecal content, spleen, liver and carcasses from 90 slaughtered ostriches from the studied farm. Also, blood serum of those animals were harvested and submitted to serum plate agglutination using commercial Salmonella Pullorum antigen. No Salmonella spp. was detected in any eggs, caecal content, liver, spleen, carcass and droppings from ostriches and rodents. However, Salmonella Javiana and Salmonella enterica subsp. enterica 4, 12: i:- were isolated from some samples of feed. The serologic test was negative for all samples. Good sanitary farming management and the application of HACCP principles and GMP during the slaughtering process could explain the absence of Salmonella spp. in the tested samples.
Keywords: Ostrich farming; Salmonella spp; Slaughterhouse; Eggs; Carcass